[Afisz. Incipit] W III-cią Roczninicę M.O. (Elbląg : [wydawca nieznany], 1947)
Afisz z programem obchodów 4-5.10.1947 r.
Keywords: Polska. -- Milicja Obywatelska -- 1945-1970 -- druki ulotne; Elbląg (Polska) -- 1945-1970 -- druki ulotne; Elbląg (Polska) -- 1945-1970 -- źródła